Harga saham ditinjau dari intellectual capital dan competitive advantage: Studi pada perusahaan otomotif dan komponen terdaftar di Bursa Efek Indonesia - Nindia Destiani Aska; Augustina Kurniasih (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
The research aims to analyze the effect of intellectual capital consisting of Value Added Capital Employee (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA) and competitive advantage on stock prices. The population in this study are all automotive and component sub-sector companies listed on the Indonesia Stock Exchange in 2021. The research data is secondary data with an observation period of 4 years. The sampling method used is purposive sampling, where from all automotive and component companies listed on the IDX, 12 companies are taken that publish financial statements and earn profits continuously for the 2016-2019 period. The data analysis method used is panel data regression then selected model is Random Effect Model. The results of this study can be concluded that stock prices can be explained or influenced by the variabels VACA, VAHU, STVA and competitive advantage of 40,95%, while the remaining amount is explained or influenced by other variabels outside the model. The results of this study partially VACA and competitive advantage have no effect on stock prices, VAHU has a positive and significant effect on stock price, STVA has a negative and significant effect on stock price.